2010
DOI: 10.1002/ddr.20367
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of xanthine oxidase‐inhibiting and free radical‐scavenging activities between plant adaptogens of Eleutherococcus senticosus and Rhodiola rosea

Abstract: The present study employed 2,2-diphenyl-l-picrylhydrazyl (DPPH) radical-scavenging and xanthine-xanthine oxidase (XO) assays to compare the antioxidant capacity between two plant adaptogens, Eleutherococcus senticosus (Araliaceae) and Rhodiola rosea (Crassulaceae). The IC 50 value for XO activity for Rhodiola was 355.4 mg/ml, while that for Eleutherococcus was 41,000 mg/ml. Eleutherococcus inhibited DPPH generation by 58.372.8% at 1,000 mg/ml, whereas Rhodiola inhibited DPPH radical by 91.172.6% at the same co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several clinical trials have confirmed its effectiveness to increase resistance to stress and fatigue (Darbinyan et al, 2000;Spasov et al, 2000;Shevtsov et al, 2003;Olsson et al, 2009). Other pharmacological effects associated with R. rosea include antiallergenic activity (Yoshikawa et al, 1996), enhancement of cognitive functions (Petkov et al, 1986), anti-depressant (Darbinyan et al, 2007) and anti-oxidant properties (Pooja et al, 2006;Calcabrini et al, 2010;Horng et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical trials have confirmed its effectiveness to increase resistance to stress and fatigue (Darbinyan et al, 2000;Spasov et al, 2000;Shevtsov et al, 2003;Olsson et al, 2009). Other pharmacological effects associated with R. rosea include antiallergenic activity (Yoshikawa et al, 1996), enhancement of cognitive functions (Petkov et al, 1986), anti-depressant (Darbinyan et al, 2007) and anti-oxidant properties (Pooja et al, 2006;Calcabrini et al, 2010;Horng et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…the eleutherosides similar to ginsenosides that have effects in the body conforming to its definition as an adaptogen [81]. Specifically, six Eleutherococcus compounds exert adaptogenic effects in the body; four of them act as antioxidants, four exhibit anticancer effects, and two show demonstrable immunostimulatory effects [82,83].…”
Section: Siberian Ginseng (Botanical Name: Eleutherococcus Senticosusmentioning
confidence: 99%